The Palgrave Handbook of Digital Russia Studies 2020
DOI: 10.1007/978-3-030-42855-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Digital Activism in Russia: The Evolution and Forms of Online Participation in an Authoritarian State

Abstract: This chapter describes how digitalization has affected activism in Russia by tracing the evolution, particularity, and the most visible forms of online activism in the context of the increasingly authoritarian Russian state. It discusses online activism in relation to “connective action” and illustrates it with two examples of contentious political activism: the anti-corruption campaign led by Alexei Navalny and the struggle to protect online communication from state surveillance by the Telegram messenger serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
0
13
0
4
Order By: Relevance
“…• цель действий -оказание влияния / давления на власть (Ермолаева и др., 2020;Teocharis, 2015), кооперация с другими гражданами и структурами гражданского общества (Никовская, 2017) или повышение осведомленности (Lonkila et al, 2021);…”
Section: материалы и методыunclassified
See 1 more Smart Citation
“…• цель действий -оказание влияния / давления на власть (Ермолаева и др., 2020;Teocharis, 2015), кооперация с другими гражданами и структурами гражданского общества (Никовская, 2017) или повышение осведомленности (Lonkila et al, 2021);…”
Section: материалы и методыunclassified
“…• действия реализуются в ходе коммуникативного взаимодействия с другими гражданами и социальными институтами (Lonkila et al, 2021);…”
Section: материалы и методыunclassified
“…The Russian opposition agreed to use the global social media platform Facebook to avoid monitoring by the state officials, although the local one, Vkontakte, was more popular at that moment in Russia. Similarly, Lonkila, Shpakovskaya, & Torchinsky (2021) have demonstrated that besides organized oppositional activism on the Russian Internet (RuNet), "non-contentious" online activism, which is related to everyday issues, such as environmental topics or LGBT rights, take place. Although these issues are not directly connected to politics, they "may become politicized when people start to view them as examples of bad governance" (Lonkila et.…”
Section: Nation-related Belonging In the Context Of Deep Mediatizationmentioning
confidence: 99%
“…Inasmuch as the 2017-2018 protests were seen as youth-dominated, they were also perceived to have largely originated on the internet-more specifically, on social network sites (hereafter: SNS) (Erpyleva 2020;A. Arkhipova et al 2018;Gabdulhakov 2020;Shomova 2022;Wijermars 2021;Lonkila, Shpakovskaya, and Torchinsky 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Though it must be noted that, for Russia, this is nothing new-the 2011-2013 protests (known colloquially as the Bolotnaya Protest after the Bolotnaya Square where much of the protesting took place) had also been coordinated and promoted largely through SNS (Vendil Pallin 2017;Wijermars 2021;Asmolov and Kolozaridi 2017;Lonkila, Shpakovskaya, and Torchinsky 2021;Enikolopov, Makarin, and Petrova 2020a;Zherebtsov and Goussev 2021;Toepfl 2018). This is scarcely a surprising circumstance if we consider that the vast majority of print and TV media have long been seized by the Russian state, with the implication that their materials must strictly follow the approved government line (Becker 2004).…”
Section: Introductionmentioning
confidence: 99%